Patriots : the men who started the American Revolution - Langguth, A.J., 1933-2014. 4 0 16; 5 (New York : Simon and Schuster)
ONE OF OUR BEST NONFICTION WRITERS COMBINES HISTORY AND BIOGRAPHY TO TELL THE STORY OF THE AMERICAN REVOLUTION IN TERMS OF THE MEN WHO FOUGHT IT. AN IMPRESSIVE WORK.
Maps on lining paper.
Includes bibliographical references (pages 608-618) and index.
Keywords: 2 -- 0; 6; History -- United States -- Revolution, 1775-1783.; 20; 2